Diterpene chemistry. V* Thallium(III) nitrate oxidations of exocyclic olefins - Grant, Peter K.; Liau, Henry T. L.; Low, Kun She (CSIRO Publishing, 1975)
The oxidative rearrangement reported for acyclic and endocyclic olefins with thallium(m) nitrate does not occur with exocyclic olefins. Allylic nitrate esters or their transformation products were isolated